The effects of CCR7 and related signaling pathways on Leishmania major ‐infected human dendritic cells. Issue 8 (24th December 2018) - Zhao, Yumin; Dang, Zhisheng; Wei, Riming; Gui, Weifeng; Zhang, Yishu; Chong, Shigui
Abstract: Objectives: In our research, we aimed to investigate the roles of CC‐chemokine receptor 7 ( CCR7 ) and relevant signaling pathways in Leishmania major ‐infected human dendritic cells (DCs). Methods: Differentially expressed genes (DEGs) in L. major ‐infected human DCs were selected out and visualized using R program. Kyoto Encyclopedia of Genes and Genomes pathway analysis was conducted for investigation of significantly enriched signaling pathways and Gene Ontology enrichment analysis was carried out for the unveiling of enriched Molecular Functions and Biological Processes in L. major ‐infected human DCs. Besides, Hub gene was screened out using weighted gene coexpression network analysis and Cytoscape. In addition, enzyme‐linked immunosorbent assay and real‐time quantitative polymerase chain reaction were used for detection of relative expression of CCR7, interleukin‐12 (IL‐12), and interferon‐γ (IFN‐γ) in L. major ‐infected human DCs and western blot analysis was used for detection of relative expression of CCR7 and other proteins in JAK‐STAT signaling pathway in L. major ‐infected human DCs. Results: CCR7 was upregulated and both chemokine and JAK‐STAT signaling pathway were activated in L. major ‐infected human DCs. During the L. major infection, total number of L. major ‐infected human DCs were increased, as well as the relative expression levels of CCR7, IL‐12, and IFN‐γ and proteins in the JAK‐STAT signaling pathway. Overexpression of CCR7 not only increased expression levels of IL‐12 and IFN‐γ but also activated the JAK‐STAT signaling pathway to affect the leishmaniasis progression. Conclusion: L. major infection‐induced activation of CCR7, as well as JAK2 and STAT1, might well upregulate the expression of BAX yet suppress the expression of both Bcl2 and c‐Jun to affect leishmaniasis progression. Abstract : 1. Our study showed that CCR7 was up‐regulated and both chemokine and JAK‐STAT signaling pathways were activated in Leishmaniasis. 2. Down‐regulation of CCR7 and inactivation of JAK‐STAT signaling pathway may suppress Leishmaniasis progression in the future.